Investigation of potential behavioral and physiological effects of caffeine on D. magna - Nunes, Bruno (2022)
With the ever-increasing consumption of pharmaceutical compounds, their presence in the environment is now an undisputable reality. The majority of these compounds are released into the wild after their therapeutic use, as biotransformation products or in their original form. The presence of this class of compounds in the environment, due to their biological properties, can exert effects on non-target organisms, with adverse consequences. In addition, some bioactive substances, such as stimulants of the central nervous system, are also used by humans as part of their diet. The adverse consequences posed by such chemicals may be permanent or transient, if the exposure to xenobiotics is halted; it is thus of the paramount importance to study effects that result from long-term exposure to toxicants, but also the recovery of organisms previously exposed to such substances, especially if such chemicals may cause some type of addiction. Caffeine (1,3,7-trimethylxanthine) is a naturally occurring alkaloid found in many plants, being one of the most common stimulant/pharmaceutical compounds found in the environment. In addition, it is addictive, and strongly consumed by humans, a factor that contributes also for its continuous presence in the aquatic environment. The aim of this study was to evaluate the effects of environmentally relevant concentrations (0.08; 0.4; 2; 10; and 50 μg/L) of caffeine on behavior and physiological parameters (that are proxies of metabolic traits, such as oxygen uptake and glycogen content), in individuals of the freshwater crustacean species Daphnia magna, of distinct ages, and with or without a recovery period in the absence of caffeine. Regarding behavior, the results indicated that caffeine exposure altered the moved distance of the test organisms, but not according to a coherent pattern; low concentrations of caffeine reduced the movement of exposed daphnids, while higher levels did not have any measurable effect on this parameter. In addition, it was possible to identify subtle withdrawal effects (animals exposed to caffeine during 21 days and kept in uncontaminated media for 2 days). Regarding the other two studied parameters, caffeine exposure did not result in any significant modification in oxygen uptake and glycogen stores/reserves of the test organisms, in animals continuously exposed, or in those subjected to a recovery period, suggesting that despite a behavioral stimulatory effect, this was not followed by any metabolic change, and no addictive effect was possible to infer. The results showed that the presence of caffeine in environmental concentrations can induce mild behavioral effects at low, albeit realistic levels, but not capable of establishing clear biochemical changes.